2017
DOI: 10.3168/jds.2017-12619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding an immunomodulatory supplement to heat-stressed or actively cooled cows during late gestation on postnatal immunity, health, and growth of calves

Abstract: Heat stress during late gestation negatively affects the physiology, health, and productivity of dairy cows as well as the calves developing in utero. Providing cows with active cooling devices, such as fans and soakers, and supplementing cows with an immunomodulating feed additive, OmniGen-AF (OG; Phibro Animal Health Corporation), improves immune function and milk yield of cows. It is unknown if maternal supplementation of OG combined with active cooling during late gestation might benefit the developing cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Most DEGs in these pathways were upregulated ( BLA-DQB, JCHAIN, DEFB, GRO1, HP ) in the mammary glands of IUHT-H compared to IUCL-H, although a couple were downregulated ( BOLA-DQB , BOLA ). These results are in concordance with immune deficits and elevated acute phase protein production observed among in utero heat stressed cattle 26 , 45 , 78 , but suggest that DNA methylation is not contributing substantially to regulation of immune-related genes in the mammary gland.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Most DEGs in these pathways were upregulated ( BLA-DQB, JCHAIN, DEFB, GRO1, HP ) in the mammary glands of IUHT-H compared to IUCL-H, although a couple were downregulated ( BOLA-DQB , BOLA ). These results are in concordance with immune deficits and elevated acute phase protein production observed among in utero heat stressed cattle 26 , 45 , 78 , but suggest that DNA methylation is not contributing substantially to regulation of immune-related genes in the mammary gland.…”
Section: Discussionsupporting
confidence: 79%
“…A recent proteomics analysis of the liver of periparturient cows heat stressed during late gestation found evidence of oxidative stress 17 . In the present study, genes contributing to superoxide metabolism, such as NOXO1 , GSTT1 , and SOD2 , were upregulated in the mammary gland of IUHT-H relative to IUCL-H. Higher levels of pro-inflammatory cytokines have been detected in peripheral blood mononuclear cells of heat stressed pregnant cows and in utero heat stressed calves have higher circulating acute phase proteins, whose production is induced by pro-inflammatory cytokines 45 , 46 . Together, these results suggest that altered DNA methylation patterns may contribute to heightened inflammatory responses and oxidative stress among in utero heat stressed cattle.…”
Section: Discussionsupporting
confidence: 45%
“…Whereas, the reduced quality of colostrum collected during summer compared with colostrum collected during other seasons has been reported, the impact of late-gestation heat stress on colostrum IgG concentration has been inconsistent in controlled studies. Some studies have reported decreased IgG (53,54), others have observed no differences in IgG (51,55) or even increased concentrations of IgG (56) in the colostrum of heat stressed dams. Regardless of these conflicting results, Monteiro et al (55) demonstrated that prenatal heat stress alters the calf 's capacity for IgG transfer rather than reducing the quality of the colostrum produced by the dam.…”
Section: Effects Of Heat Stress During the Prenatal Period On Immunitymentioning
confidence: 98%
“…Prenatal heat stress reduces the overall immune competence of calves during their postnatal life by derailing hematological parameters and cellular immune status from normal. For example, calves born to heat stressed dams, receiving colostrum from their dams, had reduced circulating plasma proteins (51), red blood cell counts, platelets and circulating hemoglobin, lower lymphocyte counts, and increased circulating concentration of acute phase proteins during the pre-weaning period relative to those born to cooled dams receiving colostrum from their dams (56). Peripheral blood mononuclear cells (PBMC) were isolated from in utero heat stressed or cooled calves' blood during the pre-weaning stage and were incubated in vitro with a mitogen.…”
Section: Effects Of Heat Stress During the Prenatal Period On Immunitymentioning
confidence: 99%
“…As these are all parts of complex comfort behaviour, total time spent lying down, the number of lying bouts, and the frequency of lying down are often studied in response to environmental factors in adult cattle 2 , 3 . Although the effect of in utero heat stress exposure on calf activity patterns 4 and on overall well-being 5 , 6 have been recently evaluated during the neonatal period, there is a paucity of information regarding biobehavioral responses to acute heat stress experienced by calves during the pre-weaning period. Commercial automatic data loggers overcome the limitation of time-consuming video-based behavioural observations in calves; 7 however, no research has evaluated lying behaviour in dairy calves during extreme heat stress events.…”
Section: Introductionmentioning
confidence: 99%